2003
DOI: 10.1023/b:jots.0000004078.93012.7d
|View full text |Cite
|
Sign up to set email alerts
|

Do patients drop out prematurely from exposure therapy for PTSD?

Abstract: Many studies have demonstrated the efficacy of exposure therapy in the treatment of chronic post-traumatic stress disorder (PTSD). Despite the convincing outcome literature, a concern that this treatment may exacerbate symptoms and lead to premature dropout has been voiced on the basis of a few reports. In this paper, we examined the hypothesis that treatments that include exposure will be associated with a higher dropout rate than treatments that do not include exposure. A literature search identified 25 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
256
7
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(295 citation statements)
references
References 39 publications
27
256
7
5
Order By: Relevance
“…PTSD patients often exhibit co-morbid depression and high rates of alcohol and drug abuse (Brady et al, 2000). Exposure therapy, the major mode of treatment for anxiety disorders, is relatively ineffective in treating PTSD (Hembree et al, 2004). Given the high prevalence of PTSD and its toll on society, it is essential to understand the mechanisms by which stress induces changes in brain function, as well as the mechanisms that perpetuate long-term expression of maladaptive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…PTSD patients often exhibit co-morbid depression and high rates of alcohol and drug abuse (Brady et al, 2000). Exposure therapy, the major mode of treatment for anxiety disorders, is relatively ineffective in treating PTSD (Hembree et al, 2004). Given the high prevalence of PTSD and its toll on society, it is essential to understand the mechanisms by which stress induces changes in brain function, as well as the mechanisms that perpetuate long-term expression of maladaptive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that worsening of symptoms during treatment is associated with poorer attendance (Tarrier et al, 1999) and that lack of symptom improvement is associated with failure to complete treatment (Back et al, 2006). However, a review of cognitive-behavioral PTSD treatment studies found no evidence of differential drop-out for particular forms of treatment (i.e., exposure vs. cognitive vs. stress inoculation vs. EMDR treatments) (Hembree et al, 2003). Further research is needed to determine how poor study retention is related to patient adverse reactions to integrated trauma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In posttraumatic stress disorder (PTSD) and obsessive compulsive disorder (OCD) it has been found that cognitive and exposure therapies are equally tolerable (Hembree et al, 2003;Van Oppen et al, 1995). Notwithstanding therapy type, it has also been suggested that manualised treatments may increase drop-out rates due to systematic procedures being less focussed on patients' concerns in the here and now (Hembree et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Still, non-response to postal questionnaires may have produced biased estimates of therapy effects (Edwards et al, 2002). For example, participants who were classified as "drop-outs" may have in fact reached their personal goals early in treatment and consequently discontinued with the study based on a decision that any further involvement would not provide additional benefits (Hembree et al, 2003). This may have led to more conservative estimates of treatment effects from an intent-to-treat perspective.…”
Section: Strengths and Limitations Of The Studymentioning
confidence: 99%